2022
DOI: 10.1017/wtc.2022.21
|View full text |Cite
|
Sign up to set email alerts
|

Head-mounted digital metamorphopsia suppression as a countermeasure for macular-related visual distortions for prolonged spaceflight missions and terrestrial health

Abstract: During long-duration spaceflight, astronauts are exposed to various risks including spaceflight-associated neuro-ocular syndrome, which serves as a risk to astronaut vision and a potential physiological barrier to future spaceflight. When considering exploration missions that may expose astronauts to longer periods of microgravity, radiation exposure, and natural aging processes during spaceflight, more severe changes to functional vision may occur. The macula plays a critical role in central vision and disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The emergence of virtual reality technology has revolutionized many fields, including sports and medicine [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Research in virtual reality has found that decision making in sub-elite soccer officials between on-field and virtual reality were indistinguishable, suggesting virtual reality offers a representative training environment [ 28 ].…”
Section: 3d Environment Virtual Reality Research For Football Officia...mentioning
confidence: 99%
“…The emergence of virtual reality technology has revolutionized many fields, including sports and medicine [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Research in virtual reality has found that decision making in sub-elite soccer officials between on-field and virtual reality were indistinguishable, suggesting virtual reality offers a representative training environment [ 28 ].…”
Section: 3d Environment Virtual Reality Research For Football Officia...mentioning
confidence: 99%
“…This can be achieved through longitudinal studies that follow astronauts before, during, and after their space missions to monitor any changes in their visual and neural health. Furthermore, the development of wearable technologies that can continuously monitor astronaut health during spaceflight can provide real-time data on any changes in visual and neural health, including the onset of SANS [ 49 , 50 , 51 ].…”
Section: Medical Diagnostic Challenges During Spaceflightmentioning
confidence: 99%
“…Current AI research for SANS is focused on building architectures for the detection of SANS and further understanding the pathophysiology of this neuro-ophthalmic phenomenon for orbital and planetary travel [ 37 ]. Research is also focused on merging extended reality technology for SANS and other ophthalmic conditions during spaceflight, which can be merged with AI techniques [ 50 , 109 , 109 , 110 , 111 , 112 , 113 ]. Additionally, as these AI models are built for austere environments, these emerging and revolutionary techniques can also be applied to areas on Earth with limited medical capabilities and resources [ 37 ].…”
Section: Future Direction and Conclusionmentioning
confidence: 99%
“…These countermeasures may include lifestyle and pharmacological interventions and modifications aimed at preserving mitochondrial health. Emerging countermeasures for SANS include the use of swimming goggles to provide a moderate increase in intraocular pressure to mitigate SANS [ 22 ], and the use of augmented reality to restore any potential losses in visual function [ 23 , 24 ]. Near-infrared light therapy may also be a useful side effect free, and non-invasive method to improve mitochondrial function during spaceflight.…”
Section: Introductionmentioning
confidence: 99%